2013
DOI: 10.1530/joe-13-0040
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate promotes bone formation by inhibiting protein prenylation in osteoblasts in rat tooth replantation model

Abstract: Bisphosphonates (BPs) are a major class of antiresorptive drug, and their molecular mechanisms of antiresorptive action have been extensively studied. Recent studies have suggested that BPs target bone-forming cells as well as bone-resorbing cells. We previously demonstrated that local application of a nitrogen-containing BP (N-BP), alendronate (ALN), for a short period of time increased bone tissue in a rat tooth replantation model. Here, we investigated cellular mechanisms of bone formation by ALN. Bone hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
1
31
0
2
Order By: Relevance
“…The osteogenic effects of Aln were suggested due to increased alkaline phosphatase (ALP) activity, mineralization and osteogenic genes, such as bone morphogenetic protein-2 (BMP-2), type I collagen (Col I) and osteocalcin (OC) in osteoblasts [5], [6], [7], [8], bone marrow-derived stem cells (BMSCs) [9], [10] and human adipocyte-derived stem cells (human ADSCs) [11]. Previous studies suggested that Aln is uptaken by endocytosis of macrophages, osteoclasts and osteoblasts, the similar way may also happen in hBMSCs [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…The osteogenic effects of Aln were suggested due to increased alkaline phosphatase (ALP) activity, mineralization and osteogenic genes, such as bone morphogenetic protein-2 (BMP-2), type I collagen (Col I) and osteocalcin (OC) in osteoblasts [5], [6], [7], [8], bone marrow-derived stem cells (BMSCs) [9], [10] and human adipocyte-derived stem cells (human ADSCs) [11]. Previous studies suggested that Aln is uptaken by endocytosis of macrophages, osteoclasts and osteoblasts, the similar way may also happen in hBMSCs [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry of Anxa5 and pSMAD1/5/8 were carried out using anti‐human Annexin V antibody (1:100, BioVision, Milpitas, CA, USA), anti‐phospho SMAD1/5/8 (Ser463/465) antibody (1:100, Millipore, Temecula, CA, USA), Alexa Fluor 594‐conjugated chicken anti‐rabbit IgG (Thermo Fisher Scientific, Waltham, MA, USA), and Alexa Fluor 488‐conjugated goat anti‐rabbit IgG (Thermo Fisher Scientific), and the sections were counterstained with 4â€Č,6‐diamidino‐2‐phenylindole (DAPI). Alkaline phophatase (ALP) and tartrate‐resistant alkaline phosphatase (TRAP) activities as markers of bone formation and bone resorption, respectively, were detected by staining assay as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the antiresorptive drug alendronate (Alen) can promote new bone formation by stimulating OB proliferation and/or differentiation, and inhibiting OC function [46]. However, there is a need to develop novel materials for the controlled release of this drug because of toxicity issues at high doses [46].…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%
“…However, there is a need to develop novel materials for the controlled release of this drug because of toxicity issues at high doses [46]. Shen et al .…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%